Civil and criminal liability in the field of transport relations: the impact of the Covid-19 pandemic. - Мінченко, Раїса Миколаївна; Мінченко, Р. М.; Minchenko, Raisa M.; Lutsyuk, Pavlo; Луцюк, Павло; Kamensky, Dmitriy; Каменський, Дмитро; Kolodin, Artem; Колодін, Артем Олексійович; Shamota, Oleksandr; Шамота, Олександр; Шамота, Олександр Володимирович (My University, 2021)
Пандемія COVID-19 змінила життя не лише багатьох людей, але й істотно вплинула на економіку окремих країн та світову економіку загалом. У світі відбулось скорочення виробничих потужностей у зв’язку із закриттям кордонів між країнами і запровадженням режиму самоізоляції. Пандемія коронавірусу порушила звичні взаємозв’язки між виробниками і користувачами і внесла серйозні зміни у сферу транспорту. Такі зміни відобразилися і на регулюванні відносин щодо притягнення до цивільної та кримінальної відповідальності за правопорушення у сфері транспортних відносин в умовах пандемії коронавірусу. З огляду на це, важливо проаналізувати трансформації цивільної та кримінальної відповідальності у сфері транспортних відносин внаслідок пандемії Covid19. Метою роботи є аналіз цивільної і кримінальної відповідальності у сфері транспорту внаслідок пандемії Covid-19. Об’єктом дослідження є цивільна і кримінальна відповідальність у сфері транспорту внаслідок пандемії Covid-19. Предметом дослідження є суспільні відносини, що виникають, змінюються та припиняються під час притягнення до цивільної і кримінальної відповідальності у сфері транспорту внаслідок пандемії Covid-19. Методологію дослідження складають такі методи як діалектичний метод, аналітичний метод, історичний метод, метод аналізу правових документів, статей та монографій, метод узагальнення, порівняння, синтезу, моделювання. В результаті дослідження буде проаналізовано зміни, що відбулися у сфері транспорту, а саме особливості притягнення до цивільної та кримінальної відповідальності за порушення у сфері транспорту під час пандемії Covid-19, а також з’ясовано проблемні питання притягнення до відповідальності у сфері транспорту та спірні аспекти врегулювання сторонами конфліктів у досудовому порядку. Також в результаті проведеного дослідження з’ясовано головні тенденції у сфері транспорту в умовах пандемії Covid-19 та проаналізовано, які зміни необхідно прийняти задля налагодження механізму притягнення до цивільної та кримінальної відповідальності у сфері транспорту внаслідок пандемії Covid-19. The COVID-19 pandemic has changed the lives not only of many people but also significantly affected the economy of individual countries and the world economy as a whole. The world has seen a reduction in production capacity due to the closure of borders between countries and the introduction of self-isolation. The coronavirus pandemic has disrupted the usual relationship between manufacturers and users and has made a major difference in transport. Such changes have been reflected in the regulation of relations regarding civil and criminal liability for offenses in the field of transport relations in a coronavirus pandemic. With this in mind, it is important to analyze the transformations of civil and criminal liability in the field of transport due to the Covid19 pandemic. The work aims to analyze the civil and criminal liability in the field of transport relations due to the Covid-19 pandemic. The object of the study is a civil and criminal liability in the field of transport due to the Covid-19 pandemic. The subject of the study is the public relations that arise, change, and end during the prosecution of civil and criminal transport in the wake of the Covid-19 pandemic. The research methodology consists of such methods as the analytical method, historical method, method of analysis of legal documents, articles, and monographs, method of generalization, comparison, synthesis, and modeling. The study will analyze the changes that have taken place in the field of transport, namely the peculiarities of civil and criminal liability for violations in the field of transport during the Covid-19 pandemic, as well as clarify the problematic issues of prosecution in the field of transport and controversial aspects pre-trial settlement of conflicts by the parties. The research also identified the main trends in the transport sphere in the context of the Covid-19 pandemic and explained what changes need to be made to establish a mechanism for civil and criminal liability in the field of transport due to the Covid19 pandemic.
Minchenko R. Civil and criminal liability in the field of transport relations: the impact of the Covid-19 pandemic / Minchenko R., Lutsyuk, P., Kamensky D., Kolodin A., Shamota O. // Amazonia Investiga. - 2021. - Vol.10. - Iss. 40. - P. 212-221. Режим доступу: https://doi.org/10.34069/AI/2021.40.04.21
Keywords: court; justice; the right to a fair trial; guarantees of human rights; the Convention for the Protection of Human Rights and Fundamental Freedoms; цивільна відповідальність; кримінальна відповідальність; порушення у сфері транспорту; пандемія; Covid-19